Validity and reliability of two near-infrared spectroscopy devices to measure resting hemoglobin in llite cyclists - Gandia-Soriano, A.; Salas-Montoro, J.-A.; Javaloyes, A.; Lorente-Casaus, C.; Zabala, M.; Priego-Quesada, J. I.; Mateo March, M. (International Journal of Sports Medicine, 2022)
A new method to monitor internal training load from muscle oxygen saturation using near-infrared spectroscopy could be of practical application for research and training purposes. This technology has been validated in different scientific fields, including sports science, and Humon Hex and Moxy are two leading brands. However, its relationship with hemoglobin has not been studied. Forty-eight professional cyclists, 19 men and 29 women, underwent a blood test to measure hemoglobin in the early morning. Immediately afterwards, hemoglobin and muscle oxygenation were monitored at rest by Moxy and Humon Hex on their right quadriceps (where the skinfold was measured). Venous blood hemoglobin was higher than the measurement for both devices (p<0.001). Both hemoglobin (p<0.001) and muscle oxygen saturation measurements (p<0.05) were higher in Humon Hex than for Moxy, and there was a reasonable reproducibility (ICC=0.35 for hemoglobin and 0.26 for muscle oxygen saturation). Skinfold had an inverse relationship with hemoglobin measurement (r=-0.85 p<0.001 for Humon Hex and r=-0.75 p<0.001 for Moxy). These findings suggest that resting hemoglobin data provided by these devices are not coincident with those of blood sample, and skinfold has an inverse relationship with blood hemoglobin measurement.